Does Free Community College Improve Student Outcomes? Evidence From a Regression Discontinuity Design. (June 2021) - Bell, Elizabeth
In this article, I utilize a regression discontinuity design to estimate the effects of Tulsa Achieves—a prevalent and understudied type of tuition-free college program. In contrast to concerns regarding tuition-free community college suppressing bachelor's degree attainment, I find that Tulsa Achieves increased the likelihood of transferring to 4-year colleges by 13 to 14 percentage points and increased bachelor's degree attainment by approximately 2 percentage points. The estimates for shorter outcomes are underpowered to detect policy relevant effects, but suggest Tulsa Achieves increased college GPA and had a null impact on credit accumulation, retention, and graduation from Tulsa Community College.